100 Just how long does it take? Using parental surveys documenting time required to provide care at home to children with medical complexity as a tool for advocacy. (19th August 2020) - Lafontaine, Audrey; Patel, Hema; St-Sauveur, Isabelle
Abstract: Background: Children with medical complexity (CMC) constitute a growing population here and everywhere. CMC are fragile, complex, and dependent on technology. Sustainable, safe and effective care at home requires a high level of parental dedication, in knowledge, skills and time. While children thrive in the home setting, the demands on caregivers are substantial. As part of a larger advocacy project, a collaboration between healthcare professionals looking after CMC in Quebec was formed with a primary goal to create evidence-based standardized guidelines for homecare practices. During this process, wide disparities in actual care support received were noted as was the paucity of publication quantifying the time it takes to care for CMC at home. This innovative survey was planned to better describe families' experiences and to further advocacy efforts with the development of data-driven care support recommendations. Objectives: The objectives of this prospective survey were: a) to quantify daily parental expenditure of time to provide care at home to their child requiring i) parenteral nutrition (TPN), ii) peritoneal dialysis (PD), iii) noninvasive ventilation (BIPAP) or iv) tracheostomy care (TC) and b) to qualitatively explore the perceptions of parents regarding existing and desired homecare supports. Design/Methods: Quebec CMC were identified through collaboration of multidisciplinary experts from each pediatric university hospital center and the provincial home ventilation program. The daily care required for CMC was described step-by-step with input from CMC's parents with either TPN, PD, BIPAP or TC. A survey was developed to estimate time required by parents for care completion related to technology, medication, enteral feeding, maintenance of equipment and care organization. Open ended questions on parental perceptions of existing and desired homecare supports were included. The surveys were sent to all eligible families by their primary pediatrician or nurse. Data were entered into a database. For each care intervention, descriptive analyses were performed to determine the median (interquartile range) time required. Thematic analyses were used to evaluate open ended responses. Summary data was used by the expert collaboration to draft data-driven homecare support recommendations for CMC in Quebec and create request template to translate the recommendations into a practical tool for advocacy. Results: A total of 87 parents of CMC were surveyed and 78 with complete quantitative data were available for analysis. For TPN, 14 surveys were available. The median (interquartile range) of total daily time dedicated to medical care was 259 (180) minutes a day, with care distributed through TPN administration and preparation (62 (49) minutes/day), enteral nutrition when indicated (42 (34) minutes/day), medication (48 (70) minutes/day) and meal (135(98) minutes/day). For PD, 12 surveys were available. Total daily time dedicated to medical care was 160 (111) minutes/day, with care distributed through dialysis administration and preparation (58 (19) minutes/day), enteral nutrition when indicated (35 (25) minutes/day), medication (35 (28) minutes/day) and other medical care (46 (24) minutes/day). For BIPAP, 39 surveys were available. Total daily time dedicated to care directly associated with BIPAP use was 18 (15) minutes/day. Total daily time dedicated to medical care was 55 (77) minutes/day when well, and 83 (180) minutes/day when sick. Respiratory care was 31 (42) minutes/day when well, and 48 (125) minutes/day when sick. Medication administration was 20 (22) minutes/day when well and 28 (60) minutes/day when sick. Personnel and equipment management was reported to take a median of 55 (interquartile range 119) minutes/week. For TC, 13 surveys were available. Total daily time dedicated to medical care was 109 (239) minutes/day, with 87 (111) minutes/days of direct tracheostomy care. Parents of CMC asked for further support in those categories: financial help, help with home task, respite, nighttime help and specialized support. Conclusion: Parents provide substantial care at home for CMC. This study provides a first look at the actual time required to perform care. Although widely distributed, those time data give a first and unique overview of the task for parents taking care of CMC. Data driven recommendations for care support at home were created, along with standardized care request templates which are now in regular use in Quebec, demonstrating a powerful tool for advocacy.